Extended-RSA for Encryption Process to Improve Application Server Availability. (August 2019) - Susanto, A; Herman; Putranto, M I; Utama, D N; Wibowo, A
Abstract: Every enterprise stores and operates its transactions confidentially, therefore it has to encrypt the transaction to protect it from data intruders. Technically, most encryption processes are ranging from hundreds of milliseconds. If there is a lot of encrypting process, then the performance will be getting bottleneck and the transaction's speed is being slowed down. In this paper, a promising scheme by adding GZIP compression on the former RSA encryption method to increase speed is proposed; thus every transaction is going to require less times, therefore the number of failed transactions or requests will be reduced. Hence, this way makes the transaction easier for customers to do. The result of little experimental test shows that using XOR to stream cipher-text to replace the absent of padding into specific bytes shows a lot of performance increase resulting other factors such as availability also affected without sacrificing the security level.